2013
DOI: 10.1371/journal.pone.0058977
|View full text |Cite|
|
Sign up to set email alerts
|

Prediction and Validation of Gene-Disease Associations Using Methods Inspired by Social Network Analyses

Abstract: Correctly identifying associations of genes with diseases has long been a goal in biology. With the emergence of large-scale gene-phenotype association datasets in biology, we can leverage statistical and machine learning methods to help us achieve this goal. In this paper, we present two methods for predicting gene-disease associations based on functional gene associations and gene-phenotype associations in model organisms. The first method, the Katz measure, is motivated from its success in social network li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
133
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(136 citation statements)
references
References 46 publications
2
133
0
Order By: Relevance
“…In addition, Yu et al [27] reported a systematic approach that efficiently integrates the chemical, genomic, and pharmacological information for multi drug targeting and discovery on a large scale, based on two powerful methods of Random Forest (RF) and Support Vector Machine (SVM). Finally, Singh-Blom et al [28] presented two methods for predicting gene-disease associations based on functional gene associations and gene-phenotype associations in model organisms, which is close to this work. Those methods are: the Katz measure, used in social network link prediction, and CATAPULT (Combining dATa Across species using Positive-Unlabeled Learning Techniques, a supervised machine learning method that uses a biased support vector machine, where the features are derived from walks in a heterogeneous gene-trait network.…”
Section: Literature Surveysupporting
confidence: 56%
“…In addition, Yu et al [27] reported a systematic approach that efficiently integrates the chemical, genomic, and pharmacological information for multi drug targeting and discovery on a large scale, based on two powerful methods of Random Forest (RF) and Support Vector Machine (SVM). Finally, Singh-Blom et al [28] presented two methods for predicting gene-disease associations based on functional gene associations and gene-phenotype associations in model organisms, which is close to this work. Those methods are: the Katz measure, used in social network link prediction, and CATAPULT (Combining dATa Across species using Positive-Unlabeled Learning Techniques, a supervised machine learning method that uses a biased support vector machine, where the features are derived from walks in a heterogeneous gene-trait network.…”
Section: Literature Surveysupporting
confidence: 56%
“…There has been an increasing amount of works on recovering gene-disease associations using networkbased algorithms [34,17,27] Gonen and Kaski [10] proposed Kernelized Bayesian Matrix Factorization (KBMF) to predict drug-target interactions by making use of the information from multiple domains via kernel methods. The Multiple Similarities Collaborative Matrix Factorization (MSCMF) [36], was proposed for drug-target interaction prediction which approximates the indicator matrix by the product of projection matrices of drug and target similarity matrices.…”
Section: Detecting Interaction Of Data Pointsmentioning
confidence: 99%
“…For each test drug, we ran a weighted majority voting among its k = 10 most similar drugs based on the cosine distances imposed over the vector representations of drugs. Following the previous work, 26 we used the "recall@top-R" as the evaluation metric, which is defined as the fraction of true associated MoAs (or targets) that were retrieved in the list of top-R predictions for a drug. The motivation of using this metric was that a method that can recover the true MoAs (or targets) in the top-R predictions with high probability is desirable and useful in applications such as drug repurposing.…”
Section: Mania Achieves Accurate Prediction Of Drug Moas and Targetsmentioning
confidence: 99%